Reformulation Of Restorative Justice Arragements That Oriented Towards Victim Protection - Ma'aruf, Deasy Mariana (Universitas Pendidikan Ganesha, 2025)
The newly enacted Indonesian Criminal Code (KUHP) introduces significant reforms, including the incorporation of restorative justice. This approach prioritizes resolving criminal cases through dialogue involving the offender, victim, families, and community, aiming for relationship restoration and substantive justice. Although its inclusion is a progressive step, the current regulation remains limited particularly in its lack of victim-centered orientation. This normative juridical research explores: (1) the construction of victims' rights in the restorative justice framework under the new KUHP; (2) weaknesses in current restorative justice regulations within Indonesia’s positive law; and (3) reformulation strategies to ensure victim protection. Findings show that restorative justice in the KUHP lacks clear standards for victim protection, such as the right to refuse, to receive consultation, and to obtain legal or psychological support. Its fragmented, sectoral application across institutions causes inconsistencies in interpretation and practice, ultimately hindering the fulfillment of victims’ rights.